About The Need for A Harmonised Labelling for Locally Produced Food: A Study of Local Food Labels in Selected EU Member States - Anna KAPALA (Communications of International Proceedings, 2021)
Consumers are increasingly interested in buying locally produced food but often cannot recognise it on the market. As the European Union has not introduced a local food labelling scheme, the study examines how selected countries defined and labelled local food and whether the implemented brands are suitable for fulfilling their functions of identifying, promoting and guaranteeing local products, avoiding misleading consumers. The question of to what extent geographical indications can be used as a tool to identify locally produced food is also considered. The analysis shows that there is a variety of local or regional, public and private brands that are the result of bottom-up initiatives and local self-governance, but their proliferation, differences in legal nature and the meaning of the messages conveyed adversely affect their function. Therefore, a harmonised labelling should be introduced at the UE level, otherwise at a national level, as a ready-made tool for promoting and distinguishing local products on the market, ensuring a uniform understanding of the label for all participants in the food chain, preventing fraud and unfair competition, and giving consumers confidence in its message.
Keywords: Short Supply Chains; Local Food Systems; Collective Marks; Geographical Indications